Impact of Continuous Cropping on the Diurnal Range of Dew Point Temperature during the Foliar Expansion Period of Annual Crops on the Canadian Prairies - Bharat M. Shrestha; Richard L. Raddatz; Raymond L. Desjardins; Devon E. Worth (Advances in Meteorology)
It is important to increase our knowledge of the role of land use in changing the regional climate. This study asked, “Has the increase in continuous cropping over the past 50 years on the Canadian Prairies influenced the daily mean and range of morning dew point temperatures (Td) during the foliar expansion period (from mid-June to mid-July) of annual field crops?” We found that there has been a general increase in the decadal average of mean daily Td and in the range of morning Td from the 1960s to the 2000s. The increase in the observed range of Td between the daily minimum value, which typically occurs near sunrise, and the late morning peak was found to be related to the increase in annual crop acreage and consequent decrease in summerfallow area. The relationship was more significant in the subhumid climatic zone than in the semiarid climatic zone, and it was influenced by whether the region was experiencing either wet, normal, or dry conditions.